2021
DOI: 10.1037/lhb0000450
|View full text |Cite
|
Sign up to set email alerts
|

Guilt status influences plea outcomes beyond the shadow-of-the-trial in an interactive simulation of legal procedures.

Abstract: Objective: More than 95% of criminal convictions in the United States are secured by guilty pleas. Our current understanding of the "deals" that lead so many to plead guilty is often tied to the shadow-of-the-trial (SoT) model, which posits that plea outcomes rely solely on the penalty discrepancy they offer (represented as: [trial conviction probability 3 trial sentence]plea sentence). This study compared the power of the SoT model to predict plea outcomes with two expanded models. Hypotheses: We hypothesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 48 publications
3
17
0
Order By: Relevance
“…Guilty participants were significantly more likely to accept the plea offer than innocent participants. This finding is consistent with previous research demonstrating a significant effect of guilt, and confers further support for extending the shadow-of-the-trial model to include guilt status as a predictor (Wilford et al, in press). That said, the false guilty plea rate even in the no COVID-information condition was still substantial.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Guilty participants were significantly more likely to accept the plea offer than innocent participants. This finding is consistent with previous research demonstrating a significant effect of guilt, and confers further support for extending the shadow-of-the-trial model to include guilt status as a predictor (Wilford et al, in press). That said, the false guilty plea rate even in the no COVID-information condition was still substantial.…”
Section: Discussionsupporting
confidence: 90%
“…Many experimental studies have found that guilty defendants are generally more likely to plead guilty than innocent ones (Redlich & Shteynberg, 2016; Schneider & Zottoli, 2019; Tor et al, 2010; Wilford, Wells, & Frazier, 2021; Wilford et al, in press). Accordingly, we predicted that guilty participant-defendants would plead guilty more frequently than innocent participants (Hypothesis 1 [H1]).…”
Section: The Innocence Problem and Plea Bargainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the finding that mock defendants in Experiment 1 regarded the aggravating evidence as overall stronger than the mitigating evidence whereas the opposite was true of attorney–client pairs in Experiment 3 suggests that the modality of asynchronous vignette studies may lead to qualitatively different results than more interactive paradigms. This discrepancy suggests a need for more immersive paradigms that may more accurately reflect the decision-making of truly self-interested decision-makers (see also Wilford et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Clarifying potential differences in the ways that innocent and guilty defendants arrive at probability estimates and how such information affects their plea acceptance thresholds is an important next step. While studying false guilty pleas can be challenging, several investigators are working on methodologies that may make it easier to generate false guilty pleas in the laboratory without sacrificing the use of real-world scenarios (Frazier & Gonzales, 2020; Wilford et al, 2020).…”
Section: Discussionmentioning
confidence: 99%